Analisis Perbandingan Kinerja Sensor Jarak HC-SR04 dan GP2Y0A21YK Dengan Menggunakan Thingspeak dan Wireshark - Iman Hedi Santoso; Arif Indra Irawan (Universitas Syiah Kuala, 2022)
Until now, Internet of Things (IoT) is a very interesting topic to research. This is due to the wide role that IoT can play in human life. This study aims to compare the performance of two sensors in an IoT-based distance detection system with the focus of the parameters being tested: sensor readings, Qos of data transmission, and power requirements. The two sensors that are the subject of comparison are HC-SR04 and GP2YA21YK. As an analytical tool, this research uses two tools, namely Thingspeak and Wireshak. The performance test results show that in terms of accuracy in determining distance, the HC-SR04 has a much better performance than the GP2YA21YK. On HC SR04, the average reading error is 0.82 cm, while on GP2YA21YK it is 14.40 cm. Meanwhile, in terms of QoS parameters, the two sensor systems show almost commensurate performance, the packet loss is both 0%, the throughput value is 37.01 kbps on HC-SR04 and 38.12 kbps on GP2YA21YK. As for the delay, the HC-SR04 sensor gives a value of 33.55 ms, and on GP2YA21YK it is 26.1 ms. Furthermore, based on power requirements, sensor systems using the HC-SR04 consume 14.36% less power than the system that use GP2YA21YK. By referring to the results of measurements and visualizations using Wireshark and Thingspeak, it can be concluded that the distance detection system using the HC-SR04 sensor is better than the system with the GP2YA21YK.